One Health timeliness metrics to track and evaluate outbreak response reporting: A scoping review. (November 2022) - Fieldhouse, Jane K.; Randhawa, Nistara; Fair, Elizabeth; Bird, Brian; Smith, Woutrina; Mazet, Jonna A.K.
Summary: Background: As the global population soars, human behaviours are increasing the risk of epidemics. Objective performance evaluation of outbreak responses requires that metrics of timeliness, or speed in response time, be recorded and reported. We sought to evaluate how timeliness data are being conveyed for multisectoral outbreaks and make recommendations on how One Health metrics can be used to improve response success. Methods: We conducted a scoping review of outbreaks reported January 1, 2010– March 15, 2020, in organizational reports and peer-reviewed literature on PubMed and Embase databases. We tracked 11 outbreak milestones and calculated timeliness metrics, the median time in days, between the following: 1) Predict ; 2) Prevent ; 3) Start; 4) Detect ; 5) Notify ; 6) Verify ; 7) Diagnostic ; 8) Respond ; 9) Communication ; 10) End ; and 11) After-Action Review . Findings: We identified 26783 outbreak reports, 1014 of which involved more than just the human health sector. Only six of the eleven milestones were mentioned in >50% of reports. The time between most milestones was on average shorter for outbreaks reporting both Predict (alert of a potential outbreak) and Prevent (response to predictive alert) events. Interpretation: Tracking progress in timeliness during outbreaks can focus efforts to prevent outbreaks from evolving into epidemics or pandemics. Response to predictive alerts demonstrated improved expediency in time to most milestones. We recommend the adoption of universally defined One Health outbreak milestones, including After Action Review, such that timeliness metrics can be used to assess outbreak response improvements over time. Funding: This study was made possible by the United States Agency for International Development's One Health Workforce–Next Generation Project (Cooperative Agreement 7200AA19CA00018).